The Representation of Peace Values in The Indonesian ELT Textbook Entitled â€œThink Globally Act Locallyâ€ for the Ninth Grade. - Ardiansyah, Rijalul Zidane; Andayani T, Made Adi; Suharjito, Bambang (EFL Education Journal, 2024)
The purpose of this study was to find out how the value of peace was represented and also what was the most dominant value of peace in the Junior High School English textbook entitled "Think Globally Act Locally". The researcher used Balasooriya's (2001) theory regarding the values of peace which were mentioned as inner peace, social peace, and peace with nature. Furthermore, this research used Critical Discourse Analysis (CDA) as a research design that focused on the visual semiotics of peace values. The research was conducted using Barthes' (1977) visual semiotics theory which used two layers of meaning, namely denotative and connotative, in analyzing visual objects. The findings showed that there were 13 images representing 3 groups of peace values, 2 of which contained 2 different peace values. Among them, the first 5 images were inner peace, the second 8 images were social peace and then followed by 2 images of peace in nature. This showed that the value of social peace was more dominant compared to other peace values.